Acute MRSA Sinusitis with Intracranial Extension and Marginal Vancomycin Susceptibility - Parvathi S. Kumar; Kenji M. Cunnion (Case Reports in Pediatrics)
Methicillin resistant Staphylococcus aureus (MRSA) is increasingly being described as a cause of acute sinusitis. We present a patient with acute MRSA sinusitis complicated by rapid intracranial extension, marginal vancomycin susceptibility (MIC = 2 mg/L), delayed drainage of intracranial abscess, and subsequent development of rifampin resistance. Given the relatively high risk of intracranial extension of severe acute bacterial sinusitis and high mortality associated with invasive MRSA infections, we suggest early surgical drainage of intracranial abscesses in these circumstances. We believe this is important given the limited intracranial penetration of currently available treatment options for MRSA, especially those with a vancomycin minimal inhibitory concentration (MIC) of ≥2 mg/L.